ECONOMIC VALUATION OF CULTURAL HERITAGE TOURISM USING THE ZONAL TRAVEL COST METHOD: A CASE STUDY OF PERGAMON ANCIENT CITY - SÜER, SEDA; SADIK, GÜLSÜM (International Journal of Contemporary Economics and Administrative Sciences, 2020)
This study evaluates the cultural heritage tourism value of Pergamon Ancient City in Turkey by using the Zonal Travel Cost method. The purpose of determining the economic value of cultural resources is to determine the value of the benefits in the rational use of resources ensuring their sustainability for transferring them to future generations. In the study, the Zonal Travel Cost method, which is one of the non-market valuation methods, was opted for attaining the economic value of Pergamon Ancient City. Therefore, 330 questionnaires were distributed among the cultural tourists visiting the site with the purpose of cultural heritage tourism. In the study, 33 zones are determined according to the distance traveled from the point of origin to the site. Multiple linear regression model was applied to estimate Zonal Travel Cost. The results indicated that the independent variables such as total spending, monthly income, gender, marital status, the number of individuals in the family, and working in the family were the effective variables in the model. According to the model, the total consumer surplus value for Pergamon Ancient City was found to be 26.741.248.677 TL.